IRT Application to Verify Psychometric Properties of the Beck Depression Inventory (BDI) (2014)
The aim of this study was to evaluate the performance of the Brazilian version of the Beck Depression Inventory (BDI) using Rasch-based person and item analysis. For this purpose, 271 participants were recruited, between 18 and 51 years of age (M=23.61; SD=6.12), 187 (69%) female and 84 men, all Brazilian college students. Participants responded to the BDI on the assessment of depressive symptoms. Results suggest the adequacy of the psychometric properties of the instrument and demonstrate the Rasch model’s applicability for clinical practices. Among the important tools offered by the Rasch model, we explore the use of the person-item map, which visually presents the intuitively understandable psychological construct along the dimensional scale of the instrument.